2014
DOI: 10.1101/gad.243675.114
|View full text |Cite
|
Sign up to set email alerts
|

BR-dependent phosphorylation modulates PIF4 transcriptional activity and shapes diurnal hypocotyl growth

Abstract: Signaling by the hormones brassinosteroid (BR) and gibberellin (GA) is critical to normal plant growth and development and is required for hypocotyl elongation in response to dark and elevated temperatures. Active BR signaling is essential for GA promotion of hypocotyl growth and suppresses the dwarf phenotype of GA mutants. Cross-talk between these hormones occurs downstream from the DELLAs, as GA-induced destabilization of these GA signaling repressors is not affected by BRs. Here we show that the light-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
201
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(211 citation statements)
references
References 71 publications
7
201
1
2
Order By: Relevance
“…CK2 phosphorylates PIF1 (Bu et al, 2011b), while BIN2 phosphorylates PIF3 and PIF4 (Ling et al, 2017;Bernardo-García et al, 2014). However, these kinases are not necessary for the light-induced phosphorylation of PIFs in vivo.…”
Section: Kinases That Phosphorylate Pifsmentioning
confidence: 99%
See 1 more Smart Citation
“…CK2 phosphorylates PIF1 (Bu et al, 2011b), while BIN2 phosphorylates PIF3 and PIF4 (Ling et al, 2017;Bernardo-García et al, 2014). However, these kinases are not necessary for the light-induced phosphorylation of PIFs in vivo.…”
Section: Kinases That Phosphorylate Pifsmentioning
confidence: 99%
“…The GSK3-like kinase BRASSINOSTEROID-INSENSITIVE (BIN2) has been shown to phosphorylate both PIF3 and PIF4 in vitro (Bernardo-García et al, 2014;Ling et al, 2017). BIN2-mediated phosphorylation promotes the degradation of PIF3 and PIF4 in the dark.…”
Section: Factors Controlling Pif Abundance Under Darknessmentioning
confidence: 99%
“…In Arabidopsis and other species, BR mutants phenotypically resemble GA-deficient plants in impaired germination (Unterholzner et al, 2015), hypocotyl elongation, dwarfism, darker green leaves, late flowering, and reduced fertility (Clouse, 2011). Numerous studies have shown that BRs and GAs interact at the signaling level Gallego-Bartolomé et al, 2012;Li et al, 2012;Bernardo-García et al, 2014). GAs signal through the degradation of the DELLA transcriptional repressors (Schwechheimer, 2012;Daviè re and Achard, 2013), which is initiated following the perception of bioactive GA by the GA receptor GID1 (Griffiths et al, 2006;Willige et al, 2007).…”
Section: Br and Ga Biosynthesis And Signaling Are Intertwined In Arabmentioning
confidence: 99%
“…A mutant form of PIF1 deficient in CK2 phosphorylation sites displayed reduced degradation in response to light in vivo, suggesting CK2 promotes PIF1 degradation. BIN2 phosphorylates PIF4 in vitro and BIN2-mediated phosphorylation affects degradation of PIF4 under light 21 . However, both CK2-and BIN2-mediated phosphorylation of PIFs are light independent, suggesting that additional kinases are necessary for light-induced phosphorylation of PIFs 22 .…”
mentioning
confidence: 99%